2001
DOI: 10.1038/sj.onc.1204696
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the TSLL1 and TSLL2 genes, members of the tumor suppressor TSLC1 gene family encoding transmembrane proteins

Abstract: We have recently identi®ed the TSLC1 gene as a novel tumor suppressor in human non-small cell lung cancers. TSLC1 encodes a membrane glycoprotein with an extracellular domain homologous to those of immunoglobulin superfamily proteins. Truncation of TSLC1 in the cytoplasmic domain in a primary human tumor suggests that this domain is important for tumor suppressor activity. Here, we report the isolation of two TSLC1-like genes, TSLL1 and TSLL2, based on their structural homology with the sequences corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 15 publications
1
63
0
1
Order By: Relevance
“…On the other hand, the cytoplasmic domain of TSLC1 is relatively short of 46 amino acids but contains a couple of important motifs, a protein 4.1-binding motif just adjacent to the transmembrane domain and a PDZ-binding motif (class II) at the carboxyterminal end (Songyang et al, 1997;Fukuhara et al, 2001;Fukami et al, 2002). We have recently demonstrated that the 4.1-binding motif is essential for the association of TSLC1 with DAL-1/4.1B, another tumor suppressor protein in lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the cytoplasmic domain of TSLC1 is relatively short of 46 amino acids but contains a couple of important motifs, a protein 4.1-binding motif just adjacent to the transmembrane domain and a PDZ-binding motif (class II) at the carboxyterminal end (Songyang et al, 1997;Fukuhara et al, 2001;Fukami et al, 2002). We have recently demonstrated that the 4.1-binding motif is essential for the association of TSLC1 with DAL-1/4.1B, another tumor suppressor protein in lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…These include the nectin-like (Necl) cell adhesion molecules, a family of immunoglobulin (Ig)-like CAMs also called the cell adhesion molecules (Cadm), the TSLC1-like proteins (Fukuhara et al, 2001) and the synaptic cell adhesion molecules (SynCAMs) (Biederer et al, 2002). Necl-1 and Necl-2 are expressed along the axon internode and are directly apposed by Necl-4, and potentially Necl-2, on the inner turn, that is, the periaxonal Schwann cell membrane (Maurel et al, 2007;Spiegel et al, 2007).…”
Section: The Internodementioning
confidence: 99%
“…TSLC1 encodes a 75 kDa N-linked glycoprotein that mediates intracellular adhesion through homophilic interactions in a Ca 2 þ /Mg 2 þ independent manner . This 75 kDa N-linked glycoprotein comprises three Ig-like C2-type domains, a single hydrophobic membranespanning a-helix and a short cytoplasmic domain of 46 amino acids that contains a protein 4.1-binding motif just adjacent to the transmembrane domain and a PDZbinding motif (class II) at the carboxy-terminal end (Songyang et al, 1997;Fukuhara et al, 2001). The 4.1 binding motif at the juxtamembrane region is essential for the interaction with the tumor suppressor protein in lung cancer, DAL-1 (differentially expressed in adenocarcinoma of the lung-1, EPB41L3), which is localized at the cytoplasmic side of the cell membrane (Tran et al, 1999).…”
Section: Introductionmentioning
confidence: 99%